Performance analysis of professional, semiprofessional, and junior elite rugby league match-play using global positioning systems - McLellan, C. P.; Lovell, D. I. (The Journal of Strength and Conditioning Research, 2013)
The aim of the present study was to examine the positional differences in physical performance measures of professional, semiprofessional, and junior elite rugby league match-play using portable Global Positioning Systems (GPSs). Twelve professional, 12 semiprofessional, and 18 junior elite male rugby league players were monitored during 5 regular-season competition matches using portable GPS software. The mean total distance traveled during professional (8,371 ± 897 m) and semiprofessional (7,277 ± 734 m) match-play was significantly (p < 0.05) greater than that traveled during elite junior (4,646 ± 978 m) match-play. Position-specific total distance traveled and distance traveled per minute of playing time were significantly (p < 0.05) less for junior elite backs (5,768 ± 765 m; 74 ± 11 m/min) and forwards (4,774 ± 564 m; 82 ± 5 m/min) in comparison to those in professional (backs: 8,158 ± 673 m; 101 ± 8 m/min and forwards: 8,442 ± 812 m; 98 ± 12 m/min) and semiprofessional (backs: 7,505 ± 765 m; 94 ± 8 m/min and forwards: 6,701 ± 678 m; 89 ± 8 m/min) match-play. Maximum running speed, maximum sprints, and total sprint distance traveled by professional players were all significantly (p < 0.05) greater than those traveled by junior elite players but not semiprofessional players during match-play. Professional backs and forwards performed significantly (p < 0.05) more maximum sprints and traveled greater total distance during match-play in comparison to semiprofessional and junior elite players. The present findings demonstrate minimal differences in the physical performance measures of professional and semiprofessional rugby league match-play. The position-specific performance characteristics of junior elite match-play indicate that current junior elite player-development pathways may not provide adequate preparation for players transitioning into professional competition.